Iron, anemia and erythrocytosis in pregnant women at highlands: risks in mothers and newborns - Gonzales, Gustavo F. (2013)
Iron is essential for health but in excess may be harmful. The living organism has ability to store and re-use the iron body and as such its requirement is small (1-2 mg absorbed/day). Hepcidin, a hormone produced in the liver, has an important role in iron homeostasis by blocking the iron transport protein and inhibiting iron absorption. Maternal anemia due to iron deficiency is a public health problem when it is moderate (7-<9 g/dL) and severe (Hb<7 g/dL) since it increases the risk of maternal and neonatal morbi-mortality. Similarly, high levels of hemoglobin during pregnancy affect the mother and newborn. In Peru, there is a National Program to supplement with iron to all pregnant women anemic or not. Scientific evidence shows that hemoglobin values between 9-10.5 g/dL are optimal for best fetal growth and that treatment with iron supplementation to non anemic women increases levels of hemoglobin, oxidative stress, and has adverse effects on the newborn. Since many populations at highlands have increased hemoglobin levels, it has been suggested to correct hemoglobin cutoff to define anemia. Several studies have demonstrated that it would not be necessary to change this cut-off as defined for population at sea level. In conclusion, studies results do not support the need for generalized iron supplementation to all pregnant women. Iron supplementation to pregnant women at high altitude should be avoided if diagnosis of anemia is not clearly demonstrated. It is recommended for each altitudinal population determining the level of anemia and body iron status before deciding to treat with iron supplements.Key words: Maternal anemia, maternal erythrocytosis, hepcidin, altitude, iron.